Recent advances in local anesthetic drug delivery systems based on natural polymers - Guo, Bing; Zhou, Qunhua; Zhang, Xiangchao; Ma, Qiuyang; Ma, Ming; Wang, Tao (Frontiers in Bioengineering and Biotechnology, 2026)
The core objective of pain management is to effectively alleviate pain while ensuring safety, sustainability, and personalization. Local anesthetics demonstrate significant advantages in analgesia, yet their clinical application is constrained by short half-lives and the risk of cardiotoxicity and neurotoxicity when administered in high doses. The development of long-acting local anesthetics with sustained-release formulations has become a research focus. Traditional carriers like liposomes often suffer from rapid initial release and drug diffusion, leading to limited analgesic duration and low drug loading capacity. Natural polymers, however, offer distinct advantages as drug delivery systems. They exhibit excellent biocompatibility and biodegradability, breaking down into harmless byproducts in the body to prevent tissue accumulation and immune reactions. With natural origins and cost-effectiveness, polymers such as chitosan and sodium alginate also demonstrate mucosal adhesion properties to prolong drug retention at injection sites. Their highly modifiable molecular structures allow chemical adaptation to different local anesthetics. Recent advancements in microfluidics and 3D printing have optimized drug loading and controlled-release performance in natural polymer composite systems, showcasing significant clinical translation potential. This review summarizes all studies on natural polymer-based local anesthetic delivery systems that include experimental validation, animal experiments, and clinical trials, sourced from PubMed and the ClinicalTrials.gov database over the past 5 years and outlines future application prospects, providing innovative approaches for long-acting analgesia.